Bayesian methods in health economics: probabilistic sensitivity analysis 4 - O'Hagan, Anthony (Henry Stewart Talks, 2009)
Economic modelling, Uncertainty in economic models, Probabilistic Sensitivity Analysis (PSA), Computing output uncertainties, Expressing output and decision uncertainty, Economic model of a new vaccine
Reviewed at 2022/03/30